Opinions of caregivers on supporting couples in perinatal bereavement at the Kintambo Maternity Hospital, Kinshasa, Democratic Republic of the Congo - Izana, Pambi Hydrogen; Kiala , Makola José; Kulembidila, Nsopa Emiliène; Lulendo , Ndiene Suzanne; Muteb , Yav Sakabong Jean Jacques; Manyama , Katata Clement; Yende , Mupepe Roland; Zaya , Bwiyi Julien; KADIATA , Bukasa Augustin (Orapuh Journal, 2024)
Introduction Maternity units are supposed to be places that welcome new life, but sometimes things do not go as hoped. Many mistakenly believe that the death of a baby, known for only a few hours or days, has less impact than the death of an older child. However, the sense of loss experienced by parents is equally profound. Purpose The objective of this study was to assess the opinions of caregivers on supporting couples in perinatal bereavement at the Kintambo Maternity Hospital in Kinshasa, Democratic Republic of the Congo. Methods This descriptive study was conducted at the Kintambo Maternity Ward in Kinshasa, focusing on caregivers’ opinions regarding the support of couples during perinatal bereavement. A survey was used to explore the issue and collect data, aiming to describe and understand the phenomenon from the perspective of those involved. Additionally, face-to-face interviews were employed as a data collection technique, allowing caregivers to express their views. Results The results show that 56% of the caregivers interviewed were men and 46% were women. However, 41% of caregivers expressed a favourable opinion regarding the support of couples during perinatal bereavement, while 59% expressed an unfavourable opinion. Furthermore, 25.4% of caregivers believed that emotional involvement is an obstacle to supporting couples, 20.3% lacked in-depth knowledge about perinatal bereavement support, 35.5% showed a lack of empathy, and 18.6% of caregivers displayed a lack of psychological stability. Conclusion Supporting a couple during perinatal bereavement is challenging and requires a range of personal skills and significant self-awareness. A caregiver, dealing with both their own emotions and those of the couple, can be a custodian of suffering. It is essential for caregivers to harness their emotions positively, using them as a strength rather than fearing them, in order to better understand and care for those in mourning.